Salivary Testosterone and Cortisol Levels in Tunisian Elderly Male Patients With Mild Alzheimer’s Disease. Implications of Musical Therapy And/Or Physical Rehabilitation - Chéour, Sarah; Chéour, Chouaieb; Kilani, Chiraz; Guemri, Aymen; Zineddine, Dawser; Khélifa, Riadh; Supriya, Rashmi; Bragazzi, Nicola Luigi; Chéour, Foued; Baker, Julien S.; Gaied-Chortane, Sabri (Frontiers in Physiology, 2022)
Changes in salivary testosterone (T) and cortisol (C) levels were assessed in elderly Tunisian male patients with mild Alzheimer’s disease (AD) subjected to music therapy and/or physical rehabilitation. Male patients with mild AD (N = 26; age = 76.23 ± 4.27 years; weight: 74.76 ± 5.36 kg) were randomly assigned into four groups for three 60-min sessions per week for 4 months; including Group1 or control group (Co) (n = 6); Group2 (n = 6), participated in physical rehabilitation (PR); Group3 (n = 7), subjected to music therapy (MT) and Group4 (n = 7), participated simultaneously in music therapy and physical rehabilitation (MT + PR). Salivary T levels increased (ηp2 = 0.7) and C levels decreased (ηp2 = 0.69), significantly (p < 0.001) in the PR, MT and MT + PR groups compared to the Co group respectively. Also, increases in salivary T levels and decreases in C levels in MT + PR group were greater compared to the other groups. MT increased T levels (p < 0.001) and decreased C levels (p < 0.05) to a greater extent than the PR group respectively. Changes in salivary T levels were positively (r = 0.83; p < 0.001) and C levels were negatively (r = -0.86; p < 0.001) correlated in the PR, MT and MT + PR groups with changes in MMSE in AD patients. This study highlights that combination of MT and PR holds potential to treat AD.